The Welfare Effects of Public Opinion Polls - Esteban F. Klor; Eyal Winter (International Journal of Game Theory, 2007)
This paper presents an experimental study of the effects of polls on voters’ welfare. The analysis shows that polls have a different effect on closely divided and lopsided divided electorates. The data show that in closely divided electorates (and only for these electorates) the provision of information on the voters’ distribution of preferences significantly raises the participation of subjects supporting the slightly larger team relative to the smaller team. This causes a substantial increase on the frequency of electoral victories of the larger team. As a consequence, we observe a steep decrease in the welfare of the members of the smaller team because they vote more often and yet they loose the elections more frequently. Polls are detrimental to aggregate welfare in closely divided electorates because the decrease in the payoffs of the minority is stronger than the increase in the payoffs of the majority. In lopsided divided electorates polls don’t have a significant different effect on the voters’ turnout conditional on their team size. We do observe an increase on the frequency of electoral victories of the larger team after the provision of information, but this is in part due to smaller teams’ members voting less frequently and saving the participation costs. As a consequence, while polls have a negative effect on the relative payoffs of the minority for these electorates as well, they have a positive effect on total welfare.